2017
DOI: 10.1016/j.ccell.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Tumor Targeting Is Enhanced by CD27 Agonists through Myeloid Recruitment

Abstract: SummaryMonoclonal antibodies (mAbs) can destroy tumors by recruiting effectors such as myeloid cells, or targeting immunomodulatory receptors to promote cytotoxic T cell responses. Here, we examined the therapeutic potential of combining a direct tumor-targeting mAb, anti-CD20, with an extended panel of immunomodulatory mAbs. Only the anti-CD27/CD20 combination provided cures. This was apparent in multiple lymphoma models, including huCD27 transgenic mice using the anti-huCD27, varlilumab. Detailed mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 58 publications
4
58
0
1
Order By: Relevance
“…183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions. 200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide. 221-224 In line with preclinical and clinical data demonstrating that multi-epitope vaccines are generally more powerful than their single-epitope counterparts, 117,225 the most common vaccination strategy employed by these studies consists in targeting simultaneously multiple TAAs (20 studies).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…183,185-187 In several instances, vaccination is further combined with standard treatment regimens including conventional chemotherapy, 117,188-191 radiation therapy, 52,192-195 and targeted anticancer agents, 196-199 or with various immunotherapeutic interventions. 200-205 The latter include (1) immune checkpoint blockers such as the anti-PD-1 mAbs pembrolizumab and nivolumab, 206-208 the anti-PD-L1 mAbs durvalumab and atezolizumab, 209-211 and the anti-CTLA4 mAb ipilimumab; 137,186,212-215 (2) immunostimulatory antibodies such as utomilumab, which stimulates TNF receptor superfamily member 9 (TNFRSF9; best known as 4-1BB or CD137) signaling, 28,216-218 or the CD27 agonist varlilumab; 28,216,219,220 and immunomodulatory agents such as lenalidomide. 221-224 In line with preclinical and clinical data demonstrating that multi-epitope vaccines are generally more powerful than their single-epitope counterparts, 117,225 the most common vaccination strategy employed by these studies consists in targeting simultaneously multiple TAAs (20 studies).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…Some potential mechanisms include survival of tumor-specific CD8 + T cells, reducing the frequency of regulatory T cells within tumors, and enhancing the function of NK cells and CD8 + CTLs (Roberts, Franklin et al, 2010). In a recent study, the potential of anti-CD27 monotherapy for cancer immunotherapy was demonstrated in murine models of lymphoma (Turaj, Hussain et al, 2017). In this study, an extended panel of immunomodulatory mAbs, either as a single agent or combined with the direct tumor-targeting mAb anti-CD20, was used to treat murine lymphoma.…”
Section: Cd27mentioning
confidence: 99%
“…Similarly, agonist mAbs targeting costimulatory molecules with potential activation of NK‐ and CTL‐based innate and adaptive immune responses represent an alternative strategy that is being investigated in clinical trials (e.g., anti‐CD27 and GITR) or reach the clinic (e.g., anti‐CD137 and OX40 mAbs; Guillerey et al, ; Makkouk, Chester, & Kohrt, ; Sanmamed et al, ; Figure ). For instance, in vivo combined administration of immunomodulatory anti‐CD27–CD20 mAbs by activation of CD8 + T and NK cells mediates the killing of multiple lymphoma tumor cells (Turaj et al, ).…”
Section: Therapies Targeting Nk Cellsmentioning
confidence: 99%